Análise do crescimento da confiabilidade dos segmentos de uma máquina de lingotamento contínuo - Silva, Reinaldo de Arruda (2017)
In a steelmaking plant, the decision making for maintenane results optimization are almost always based on the experience of professionals and supported by methodologies and tools, such as Pareto, associated with the classic maintenance techniques: corrective, preventive and predictive. The concepts of Reliability Centered Maintenance (RCM) or Failure Modes and Effects Analysis (FMEA) are applied to generate work plans and predict the allocation of resources, in order to prevent or mitigate the effects of an unwanted failure and to preserve the company's assets. One of the ways to improve the results on continuous casting machines is to increase the segment's campaign based on the values obtained on previous years. However, the reference value is always based on experience, and the risks of failure will only be identified after the occurrence of the flaws, which may compromise the maintenance sector's strategies. This work proposes a more quantitative evaluation, based on the existing database on the Pareto analysis of failures of a machine’s segments, in order to set a measure for the reliability of each group of segments and verify if the actions in course are resulting in an improved reliability of the machine. Reliability analysis tools such as Weibull ++, RGA and BlockSim from RealiaSoft's Synthesis Platform are going to be used due to their well-functioning with continuous probability distributions and applications on equipment life-time and failure estimation studies, using various probability distributions. The results show that reliability growth did not occur in all groups of segments as expected and confirming the importance of reliability analysis growth to define and targeting of actions to obtain maintenance results.